A comprehensive analysis of association process for IEEE 802.15.4 wireless networks. (10th June 2014) - Chong, Jo Woon; Hwang, Ho Young; Sung, Dan Keun; Nam, Yunyoung
In this paper, we analyse the association procedure of IEEE 802.15.4 ZigBee devices and propose efficient association algorithms which associate ZigBee devices with a piconet coordinator (PNC) with changing CSMA/CA MAC parameters adaptively to the number of unassociated ZigBee devices. The proposed analysis model is based on Markov chain and order statistics concepts and the proposed association algorithms are based on a dynamic estimation concept. Simultaneous association requests from ZigBee devices delay total association time due to increased collisions among association request and data request commands. The proposed association algorithms adaptively allocate MAC parameter values based on dynamic estimation of the number of unassociated devices. Numerical results show that analytical results match well with simulation results and the proposed association algorithms shorten total association time compared to conventional algorithm. A ZigBee network with the proposed association algorithms accommodates approximately 1.5 times more users than that with the conventional one.